The Integer-antimagic Spectra of Graphs with a Chord - Richard Low; Dan Roberts; Jinze Zheng (Theory and Applications of Graphs, 2021)
Let $A$ be a nontrival abelian group. A connected simple graph $G = (V, E)$ is $A$-antimagic if there exists an edge labeling $f: E(G) → A \setminus \{0\}$ such that the induced vertex labeling $f^+: V(G) → A$, defined by $f^+(v) = \sum_{uv\in E(G)}f(uv)$, is injective. The integer-antimagic spectrum of a graph $G$ is the set IAM$(G) = \{k\;|\; G \textnormal{ is } \mathbb{Z}_k\textnormal{-antimagic}$ $\textnormal{and } k ≥ 2\}$. In this paper, we determine the integer-antimagic spectra for cycles with a chord, paths with a chord, and wheels with a chord.